Dry machining and minimum quantity lubricant of aluminum alloy 6061-t6 using coated carbide tools - Nur Amirra, Rashid (2013)
This report describes the cutting performance of different coated carbide cutting tools on surface roughness during machining of aluminum alloys AA6061-T6 using dry machining and minimum quantity lubricant (MQL) technique. The cutting speed, depth of cut and feed rate were the selected input parameters in this study. This experiment was conducted based on central composite design (CCD) method. To develop a model of process optimization based on the response surface method. The investigation results showed that MQL technique lowers the surface roughness values compared with that of conventional dry cutting conditions. Based on the investigations of the surface roughness conditions and material removal rate, MQL technique reduces the cutting temperature to some extent. This caused the surface roughness value to lower while dry machining is dependent on the heat to get better surface roughness result. In summary, the improvement in surface finish is achieved utilizing higher feed rate, medium depth of cut, lower speed and lower MQL flow rate